Studies on the susceptibility of ostriches (Struthio camelus) to the Indonesian velogenic strain of Newcastle disease virus - ., Darminto; Bahri, Sjamsul (Indonesian Animal Sciences Society, 1998)
Susceptibility of ostriches (Struthio camelus) to the Indonesian velogenic strain of Newcastle disease virus (NDV) was evaluated by artificial infection . Twelve - 5 to 6 week old ostriches were divided into 3 groups each containing 4 birds . The first group was inoculated through respiratory system by dropping directly the virus solution into the nostrils, while the second group was inoculated through digestive system by dropping directly the virus solution into the oesophagus, with the dose of infection 106ELDSo (50%-embryo lethal dose) per bird . Meanwhile, the third group was treated as uninfected control . All infected birds developed antibody responses, but only two inoculated birds from the first group and two inoculated birds from the second group developed clinical signs of Newcastle disease (ND), with no specific pathological alterations . Infected birds, either sicks or healthy, excreted the challenge viruses through the respiratory system and still be detected up to the end of this experiment, ie . 15 days post-inoculation . The challenge viruses can be re-isolated from the brain, trachea, lungs, heart, liver, spleen, kidneys, small intestine, cecal-tonsil, and proventriculus of the infected birds . This study concludes that: (1) the ostriches are susceptible to the infection of the Indonesian velogenic strain ofNDV; (2) all infected birds developed immune responses, but only half of them develops el jtigi aj i disease ; (3) the infected birds excreted the challenge viruses for a considerable long time which may play role as the Mginiseti.ce ofinfectron the other healthy ostriches ; and (4) the challenge viruses can be re-isolated from various organs of the birds . . Â Keywords : Newcastle disease vir4, 9strich, immune response, artificial infection